PENEGAKAN HUKUM TERHADAP ANGGOTA KEPOLISIAN YANG MENGGELAPKAN BARANG BUKTI DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - Muslimin, Muslimin; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Lately we know that the purpose of criminal law in general to protect the interests of individuals and protect the interests of society and the state is the need toagainst members of the police who commit criminal acts in the legal area of the Riau Regional Police General Criminal Investigation Directorate. The purpose of writing this essay, namely; First, to find out the criminal liability of members of the Police who are confirming evidence in the jurisdiction of the Riau Regional Police, Second, To find out the obstacles in law enforcement of members of the Police in the Riau Regional police law that darken the evidence, Third, To find out how to overcome obstacles in enforcement the law of a member of the Police in the jurisdiction of the Riau Regional police who embezzled evidence. The research method used in this study is a type of sociological research, namely by interview method in the Riau Regional Police.From the results of the study, based on three formulations the problem can be concluded. First, the act of embezzlement of evidence carried out by police officers in the territory of the Riau regional police, is clearly an act that is contrary to the law and should be punished in accordance with the applicable laws and regulations. However, the people cannot do much and tend not to dare to report the embezzlement of evidence carried out by these police officers, causing acts of embezzlement that cannot be processed further. Second, Constraints in law enforcement that occur against members of the police who darken the evidence, namely the mental attitude of the police themselves who lack legal awareness and tend to feel comfortable with the actions taken, and the absence of reports from victims due to lack of understanding of the victims of the law . So that this is a major obstacle in law enforcement against criminal acts committed by members of the Third Police, Efforts to overcome obstacles in law enforcement by members of the police in the Riau regional police, identifying and taking effective steps to eradicate police members involved in criminal acts of embezzlement, cracking down on the state civil apparatus involved in the crime of embezzlement of evidence, conducting more in-depth investigations to capture the involvement of other persons, asking the heads of agencies to implement information technology-based service systems to reduce direct relations between officers and the public , providing broad access to the public to service standards transparently. Improving the internal control system to prevent police members from committing criminal acts, especially embezzlement of evidence.Keywords: Law Enforcement - Police - Darkening - Evidence